2023
DOI: 10.1177/00185787231159578
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Multifaceted Intervention on Antibiotic Prescribing for Cystitis and Asymptomatic Bacteriuria in 23 Community Hospital Emergency Departments

Abstract: Background: Urinary tract infections (UTIs) are over-diagnosed and over-treated in the emergency department (ED) leading to unnecessary antibiotic exposure and avoidable side effects. However, data describing effective large-scale antimicrobial stewardship program (ASP) interventions to improve UTI and asymptomatic bacteriuria (ASB) management in the ED are lacking. Methods: We implemented a multifaceted intervention across 23 community hospital EDs in Utah and Idaho consisting of in-person education for ED pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A multimodal AMS initiative decreased outpatient usage of fluoroquinolones for cystitis by 39% [40] in a large health system of Texas from 2016 to 2018, and a similar effort in Colorado, US, was more successful in encouraging the use of nitrofurantoin as a first-line therapy for acute uncomplicated cystitis [139]. The overuse of OAT was also noted in a retrospective study of Medicare Part B enrollees in the New York State between 2016 and 2017, which found that, although AMS efforts slightly reduced the use of oral fluoroquinolones for uncomplicated cystitis, there was still a need for additional outpatient AMS efforts to curtail the use of oral fluoroquinolones in American hospitals [41,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multimodal AMS initiative decreased outpatient usage of fluoroquinolones for cystitis by 39% [40] in a large health system of Texas from 2016 to 2018, and a similar effort in Colorado, US, was more successful in encouraging the use of nitrofurantoin as a first-line therapy for acute uncomplicated cystitis [139]. The overuse of OAT was also noted in a retrospective study of Medicare Part B enrollees in the New York State between 2016 and 2017, which found that, although AMS efforts slightly reduced the use of oral fluoroquinolones for uncomplicated cystitis, there was still a need for additional outpatient AMS efforts to curtail the use of oral fluoroquinolones in American hospitals [41,49].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cystitis can dilate the tight junctions of the inflamed urothelium [12,65,82] to reportedly cause a four-fold rise in creatinine reabsorption [55,67] via passive paracellular diffusion, and the resulting decline in the urine creatinine levels can potentially introduce errors in the estimation of the renal function status of cystitis patients, leading to their under-and overdosing of OAT [25,113]. Given that every dose of an OAT regimen produces an initial subtherapeutic concentration in urine [122] during the intended build-up to the MIC, which is itself indeterminable, there is an inevitable period of potential AMR risk with the initiation of OAT, even with AMS [40,41,[137][138][139]. Thus, our root cause analysis (studies listed in Table 1) identifies the initial delay in the MIC as the root cause of AMR, which is a risk with every treatment course of OAT for cystitis.…”
Section: Root Cause Analysis Of Amr-delay and Variability In Urinary Micmentioning
confidence: 99%
“…We performed two cross-sectional evaluations 6 , 7 of antibiotic prescribing for UTI in 23 EDs in Utah and Idaho (14 to 503-bed hospitals; 9 rural, 14 urban) in the Intermountain Healthcare system, an integrated not-for-profit network of hospitals and clinics. Briefly, these studies included adult patients with an ED visit in 2017 or 2021 who had a urinalysis (UA) ordered, were diagnosed with “UTI” (identified via ICD10 code), and were discharged with an antibiotic prescription.…”
Section: Methodsmentioning
confidence: 99%